Safety of thrombolytic treatment in patients with central venous cannulation. - Lee, H. S. (1995)
OBJECTIVES--To determine the safety of thrombolytic treatment in patients with central venous cannulation. BACKGROUND--Thrombolytic treatment significantly reduces mortality in patients with myocardial infarction. Because of the fibrinolytic state induced and the potential for haemorrhagic complications, thrombolysis is currently considered a strong relative contraindication in patients who have had central venous cannulation. There are few data available to support this practice. METHODS--Complications in 56 consecutive patients admitted between 1989 and 1992 with infarction and who had cannulation shortly before, or within 24 h of thrombolysis were studied. RESULTS--Central venous access was achieved via the subclavian route in 52 patients, the internal jugular in three, and the supraclavicular in one. The main indications were for inotropic drugs in 15 patients, pacing in 17, amiodarone infusion in 19, and pressure monitoring in five. Minor haemorrhagic complications occurred in five patients. Two of these patients required either blood or plasma transfusion. Possible major haemorrhagic complications occurred in one patient who became hypotensive shortly after cannulation. Two further patients with severe cardiac failure became hypotensive after cannulation but there was no radiological evidence of effusion and the hypotension was attributed to worsening cardiac failure. Importantly, none of the 19 patients who had cannulas for amiodarone infusion developed significant bleeding complications. CONCLUSION--Central cannulation in the fibrinolytic state is associated with a low incidence of important bleeding complications. Thrombolysis should not be withheld in these patients. Cannulation via the subclavian route, however, should be avoided in patients undergoing thrombolysis.